Yield components in wheat as a function of temperature during spikelet differentiation stage - Fioreze, Samuel Luiz; Vacari, Jonathan; Turek, Thais Lemos; Michelon, Luiz Henrique; Drun, Robson Pelissari (Revista de Ciências Agroveterinárias, 2019)
A limiting factor for wheat crop expansion or off-season crop in the Brazilian Cerrado is the occurrence of elevated temperatures during cropping cycle. This study aimed to evaluate the effects of temperature during the spikelet differentiation stage on biometric and productive parameters of wheat cultivars. A greenhouse experiment was carried out under a randomized blocks design, organized in a 2 x 4 factorial scheme, with four replicates. Two day/night thermo periods (16/9 ˚C and 25/16 ˚C) were applied in four wheat cultivars (BRS 394, BRS 331, BRS Parrudo and BRS Guamirim) during the spikelet differentiation stage. Yield components were determined for individual tillers and for the whole plant. Both thermo periods do not affect yield components of wheat, either morphological and productive uniformity of tillers, which show large variation among wheat cultivars.